Difficulties of mechanical engineering students in developing integrated knowledge for the cross-discipline of mechatronics : a conceptual investigation. - Bailey-McEwan, Michael (My University, 2010)
Mechatronics is a modern interdisciplinary engineering field, embracing the traditional disciplines of mechanical and electrical / electronic engineering, as well as control and information technology, in producing automated, easy-to-use, multi-functional products and systems for domestic, commercial and in-dustrial use. It has been the candidate’s experience, corroborated by other universities’ experiences, that mechanical engineering students in a first mechatronics course (in their third year of study) have considerable difficul-ties in grasping the common principles governing the behaviour of mechani-cal and electrical devices – especially in the course’s laboratory project reflect-ing the applied nature of mechatronics. This project seeks to conceptually analyse the causes of these difficulties, and posit suitable remedies. Drawing upon the theories of Basil Bernstein, an educational sociologist, sug-gests that a first- and second-year mechanical engineering curriculum com-prising subjects by discipline recontextualises engineering knowledge from production (engineering practice) to education as a collection-type educational code that does not emphasise the commonality of the principles governing dif-ferent physical systems. In turn, this suggests that the corresponding form of knowledge tending to develop in the student is a Bernsteinian horizontal knowledge structure – a collection of sub-disciplinary bodies of knowledge that link uneasily only at their boundaries. The conceptual development theory of Lev Vygotsky, a cognitive psychologist, suggests that such collection-type horizontal knowledge structures do not attain true conceptual level, but are ‘complexes’, where the links between knowledge bodies are on the basis of common, perceived factual features. Such knowledge structures are not ade-quate for mechatronics; the grasp of common principles demanded by this cross-discipline requires a Bernsteinian hierarchical knowledge structure. Here, bodies of disciplinary knowledge are subsumptively integrated under common principles, so this structure amounts to a Vygotskian system of true concepts connected by abstract, logical relations of generality. For mechatronics, a suitable system of true concepts connected by relations of generality exists in the conceptual tool of bond graphs. These reveal the common governing principles of different physical systems by representing them as interconnected components handling various forms of energy through general effort and flow variables. The ‘Double Move in Teaching and Developmental Learning’ of the develop-mental psychologist Mariane Hedegaard seems a promising way of aiding students’ horizontal knowledge structures to develop into the desired hierar-chical knowledge structures in mechatronics. A welcome opportunity arose in 2009 to begin (in contrast to previous years) the third-year mechatronics iv course with its laboratory project, and thus with one key feature of the ‘Dou-ble Move’: problem-solving by situationally necessitated research activities. A hoped-for increase in students’ motivation was not detected, but the project was most frequently cited as the most valuable aspect of the course. Further work, by empirical research, should be carried out to test the validity of these conceptual analyses and posited remedies.